Neutral Polysaccharides From Hohenbuehelia serotina With Hypoglycemic Effects in a Type 2 Diabetic Mouse Model - Liu, Qinghong; Wu, Jing; Wang, Peng; Lu, Yuxiao; Ban, Xinhe (Frontiers in Pharmacology, 2022)
The neutral polysaccharides (NHSP) from mushroom Hohenbuehelia serotina, was purified by D301/D152 large aperture ion exchange resin chromatography and DEAE-Cellulose anion exchange chromatography. Weight-average molecular weight (MW) and Number-average molecular weight (Mn) of NHSP were 1,821 kDa and 820.55 kDa respectively. Monosaccharide component analysis showed that NHSP was composed of glucose, galactose, and mannose in molar ratio 2.6: 2.1: 1.0. FT-IR and NMR (1H and HSQC) spectroscopic analyses revealed that NHSP contained mainly 1,3-linked β-D-glucose, 1,4-linked β-D-glucose, 1,6-linked β-D-mannose, 1,6-linked α-D-mannose, 1,6-linked β-D-galactose. The thermogravimetric analysis (TGA) showed that NHSP has good thermal stability under 250 °C. NHSP notably reduced blood glucose level (hypoglycemic effect) at dose 200 mg/kg for 21 d in a type 2 diabetic mouse model. And, NHSP reduced liver index significantly, suggesting that NHSP may help prevent hepatic steatosis or hepatomegaly.